Influence of the Automated Configuration System on the Change Management Process of the IP Area of a Mobile Operator in Peru During the COVID-19 Pandemic - Romero Lovera, Jesús Alonso (2022)
The objective of this research was to determine the influence of the automated configuration system on the change management process of the IP area of a mobile operator during the COVID-19 pandemic. A quantitative, experimental, applied, explanatory approach was used on a population and sample consisting of change management efforts between the years 2019 and 2020. The failure rate of change requests decreased from 74.95% in 2019 to 59.86% in 2020 and the success rate of change requests increased from 25.05% to 40.14% also, the system is resilient due to the fact that the success rate increased by 16.30%. It is therefore concluded that the automated system of configurations has a positive influence on the management process with a success rate increase of 60.28% and a failure rate decrease of 20.14%.